57 Improving the reporting of medical risks and benefits in the media: the press alert app. Issue Volume 23:Issue Supplement 1(2018) (June 2018) - Freeman, Alexandra; Finikarides, Leila; Pearson, Mike; Spiegelhalter, David
Abstract : Objectives: Papers, press releases and headlines very commonly still cite relative risks only, leading to headlines such as a drug or behaviour 'halves your risk of' or 'doubles your risk' of an effect. These headlines sound dramatic, but leave the reader none the wiser of the actual magnitude of either the risk or the effect. This is despite the fact that many journals now require authors to give the numbers for absolute as well as relative risks (or benefits). The reasons for this failure to use absolute risks are often that they are not available, or that journalists and press officers lack the confidence to convert the numbers they have been given to the numbers they wish to report. We are designing and currently user-testing an App to represent the findings of research clearly and accurately, for use by journalists and publishers. Method: Registered press officers will have password-protected access to a web front-end allowing them to create a press alert via the App. The interface will help them input correct absolute risk data from the research paper (or, with the authors, source it externally). They will also be include a link to their full press release. When a press alert has been completed, the App will push a notification to the phones of all registered journalists who have it (pre-embargo). The App will display the results of the study in terms of absolute and relative risks as well as 'number needed to treat' in various graphical, numerical and verbal formats. Journalists can use these directly in their publications and stories, and follow the link to the full press release. We aim to evaluate the App's effects, monitoring story uptake volume, reporting of absolute risks and proportion of stories including caveats about interpretation. Results: N/A. Conclusions: This App could form an efficient conduit between academics (and their press officers) and journalists, carrying accurate and automated graphics/phrases designed to clearly represent their results. The advantages to press officers and authors is instant access to the phones of relevant journalists. The advantages to journalists is instant push-notification of new press releases alongside easily re-used phrases, numbers and graphics for their stories. Our evaluation will determine how being explicit about absolute risks changes reporting emphasis. Other work we are currently undertaking on the effect of absolute risks on public perception of a story will be complementary to this.